Marination increases the bioavailability of lead in game meat shot with lead ammunition. (6th April 2021) - Schulz, Kirsten; Brenneis, Franziska; Winterhalter, Richard; Spolders, Markus; Fromme, Hermann; Dietrich, Silvio; Wolf, Petra; Gremse, Carl; Schafft, Helmut; Pieper, Robert; Lahrssen-Wiederholt, Monika
Abstract: As a consequence of the toxicological lead characteristics, a reduction of its exposure should consider all sources. Game meat might contain elevated levels of lead due to the use of lead ammunition. The aim of the present study was to investigate the effects of acidic marination on the bioavailability of ammunition-derived lead in game meat (Roe deer), using the growing pig as an animal model. Furthermore, the study should provide evidence that the large-area scattering of lead particles leads to noticeable differences in the individual lead intake per game meat portion. Pigs of group A ( n 7) received lead-shot game meat, which was cooked in water. Pigs of group B ( n 7) received lead-shot game meat, which was first marinated (wine and vinegar) and then cooked. The lead content of both game meat preparations was equal with 0⋅77–0⋅79 mg Pb/portion. Pigs of group C ( n 4) received lead-free game meat, which was also marinated and cooked. Additionally, lead acetate was administered intravenously to group D pigs ( n 4). Blood samples were taken on elevated time points before and after game meat intake/i.v.-application. The acidic marination increased the bioavailability of orally ingested lead, resulting in significantly higher blood lead concentrations. The bioavailability of lead was 2⋅7 % when game meat was just cooked and 15 % when the meat was marinated before. The considerable variation of the individual blood lead concentrations suggests that an inhomogeneous distribution of ammunition-derived lead particles (in terms of size and number) causes individually non-comparable lead intakes from the consumption of game meat.